2010
DOI: 10.1021/jm100739n
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Benzoxazepines vs 1,5-Benzodiazepines. One-Pot Microwave-Assisted Synthesis and Evaluation for Antioxidant Activity and Lipid Peroxidation Inhibition

Abstract: Amino-1,5-benzoxazepines 2 and 5 and hydroxyl-1,5-benzodiazepines 3 and 6 have been synthesized in one-pot solvent-free conditions from 2,3-diaminophenol and ketones through microwave assisted acid catalysis, the benzoxazepine/benzodiazepine ratio depending on the R(1) and R(3) aryl substituents. The otherwise inaccessible and unknown 2,2-dimethyl-4-aryl-1,5-benzodiazepines 8 were also prepared in an analogous manner. The reaction mechanism was investigated by means of DFT calculations. Structural assignments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 53 publications
(42 reference statements)
1
31
0
Order By: Relevance
“…A recent study aiming at developing a common approach to 1,5-benzoxazepines and 1,5-benzoazepines from the condensation of 2,3-diaminophenol with carbonyl compounds through MW-assisted solvent-free conditions has revealed several interesting features [54]. A recent study aiming at developing a common approach to 1,5-benzoxazepines and 1,5-benzoazepines from the condensation of 2,3-diaminophenol with carbonyl compounds through MW-assisted solvent-free conditions has revealed several interesting features [54].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study aiming at developing a common approach to 1,5-benzoxazepines and 1,5-benzoazepines from the condensation of 2,3-diaminophenol with carbonyl compounds through MW-assisted solvent-free conditions has revealed several interesting features [54]. A recent study aiming at developing a common approach to 1,5-benzoxazepines and 1,5-benzoazepines from the condensation of 2,3-diaminophenol with carbonyl compounds through MW-assisted solvent-free conditions has revealed several interesting features [54].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, they might be able to behave as hybrid molecules in terms of biological activity. Therefore, some of the new compounds were screened for their antioxidant activity according to a previously reported methodology, 23,24 and more specifically, for their reducing ability (RA) by interaction with the stable free radical 1,1-diphenylpicrylhydrazyl (DPPH) and for their inhibition on lipid peroxidation by interaction with the water soluble azo compound 2,2''-azobis(2-amidinopropane) dihydrochloride (AAPH) and the results are compared to well known antioxidant agents e.g. nordihydroguairetic acid (NDGA), and 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (trolox).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Condensation of azepan-4-ones with 3,5-dinitro-1-methylpyridin-2-ones in the presence of ammonia [144] was found to be a highly efficient method (40-120 • C, 0.5-2 h) for the synthesis of 3-nitro-6,7,8,9-tetrahydro-5H-pyrido [3,2- Amino-1,5-benzoxazepines and hydroxy-1,5-benzodiazepines could be synthesized using solvent-free conditions from 2,3-diaminophenol and 2,3,4-trisubstituted acetophenone though microwave-assisted (80 or 240 W, 2-3 min) acid catalysis (AcOH) [145]. It was shown that the benzoxazepine:benzodiazepine ratio depended on the three aryl substituents of acetophenone.…”
Section: Seven Membered Heterocycles With Two Heteroatoms: Microwave-mentioning
confidence: 99%